Analisis Pemikiran Ibnu Khaldun Terhadap Konsep Pendidikan Islam Perspektif Modern - Akmal Hadi; Silfia Hanani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This article summarizes the profile and views of education according to Ibnu Khaldun, a leading Muslim philosopher and sociologist. Ibnu Khaldun emphasized the importance of education in helping humans recognize their identity and understand their existence as creatures of Allah. Even though humans are equipped with reason, education has a crucial role in directing human behavior in accordance with Islamic norms. In the study of Islamic education, Ibnu Khaldun explained teaching methods, curriculum and pedagogical thinking which are closely related to Cultural Structure. This paper uses a library study approach to formulate Ibn Khaldun's views on Islamic education by referring to works such as the Muqaddimah and As-Sifa'. In this research, Ibnu Khaldun reveals important concepts about the role of educators, learning methods, and educational evaluation which are still relevant today. The analysis of this paper displays continuity between Ibn Khaldun's views and modern theory, which emphasizes the holistic development of human potential and spiritual values in education. This research provides relevant and in-depth insight into Ibn Khaldun's thinking regarding education, showing how his ideas regarding humans, curriculum, teaching methods, and educational evaluation still have strong relevance in the current educational context.